Are we speaking the same language? Call for action to improve theory application and reporting in behaviour change research - Taylor Willmott; Sharyn Rundle-Thiele (BMC, 2021)
Abstract Inconsistencies are evident in definitions and interpretations of theory, application of theory, and reporting of theory use within the behaviour change field impeding cumulative knowledge advancement. Standardised frameworks and methods are needed to support the definition, application, and reporting of theory, and to assist researchers in understanding how theory should be applied to build cumulative knowledge over time. Progress is being made with the development of ontologies, taxonomies, methods for mapping interventions, and coding schemes; however, consolidation is needed to improve levels and quality of theory use, and to facilitate the translation of theory-driven research in practice. This paper discusses the importance of rigorous theory application and reporting in health-related behaviour change research and outlines the need for a standardised framework that supports both researchers and practitioners in designing, implementing, and evaluating theory-driven interventions in a concrete and consistent manner. To this end, several recommendations are provided to facilitate the development of a standardised framework that supports theory application and reporting in the behaviour change field. Concrete and consistent theory application and reporting will permit critical appraisal within and across studies, thereby advancing cumulative knowledge of behaviour change over time.